Effect of Kinesio Taping on Pain Reduction in Carpal Tunnel Syndrome Patients: Meta-Analysis - Lely Tri Pangesti; Mehdya Vikia Murti (Journal of Health Promotion and Behavior, 2022)
Background: Carpal Tunel Syndrome (CTS) is the most common nerve compression. Some cases of CTS have chronic symptoms. The most common complaint is "Nocturnal Acroparesthesia", which is tingling pain at night. Physiotherapy interventions can be done to relieve CTS complaints, one of which is the use of Kinesiotaping. This study aims to analyze the effect of Kinesiotaping on pain reduction in patients with carpal tunnel syndrome from several previous studies.Subjects and Method: This article is a systematic and meta-analytical study. The study used the PICO model as follows. Population= Patients with Carpal Tunel Syndrome, Intervention= Kinesio taping, Comparison= No Kinesiotaping, and Outcome= Pain Reduction. The articles used in this study were obtained from several databases including PubMed, ScienceDirect, Semantics and Google Scholar. Articles are collected in a month. The keywords to search for the article were as follows: kinesiotaping OR "kinesio tape" OR pain OR "carpal tunnel syndrome" AND "Randomized controlled trial". The articles included in this study.Results: There are 8 articles included in the meta-analysis research. These eight articles from several countries including Turkey, USA, Poland, Egypt, and the Republic of Korea showed a significant reduction in Carpal Tunnel Sundrom pain (SMD= -1.122; 95% CI= -1.93 to -0.32; p <0.001).Conclusion: The use of kinesio taping can reduce pain in patients with Carpal Tunnel Syndrome.Keywords: kinesio taping, reduction of pain, carpal tunnel syndrome.Correspondence:Lely Tri Pangesti. Diploma IV of Occupational Health and Safety, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: lellytrip@gmail.com Mobile: +6282223360202.Journal of Health Promotion and Behavior (2022), 07(04): 313-321DOI: https://doi.org/10.26911/thejhpb.2022.07.04.04